Reactivations of Latent Viral Infections Are Associated with an Increased Thr389 p70S6k Phosphorylation in Peripheral Lymphocytes of Renal Transplant Recipients - Cherneha, Maxim; Korth, Johannes; Kaulfuss, Meike; Trilling, Mirko; Widera, Marek; Rohn, Hana; Dolff, Sebastian; Babel, Nina; Hörning, André; Kribben, Andreas; Witzke, Oliver (Viruses, 2021)
Reactivations of BK polyoma virus (BKPyV) and human cytomegalovirus (HCMV) frequently cause life- and graft-threatening complications after renal transplantation. Both viruses are dependent on the mTOR pathway for replication. In this study we investigated the association of viral replication with mTOR activity in peripheral lymphocytes of renal transplant recipients. A flow-cytometry based assay for the measurement of Thr389 p70S6k phosphorylation, a surrogate marker of the mTOR pathway was established. Forty-eight adult renal transplant recipients were recruited to measure p70S6k activity in their peripheral blood mononuclear cells. This data set in conjunction with information concerning previous replication of BKPyV and HCMV was examined for correlations. Episodes of BKPyV replication were significantly associated with increased p70S6k phosphorylation in CD4+ T lymphocytes (p = 0.0002) and CD19+ B lymphocytes (p = 0.0073). HCMV infection of patients with a high-risk HCMV constellation of donor and recipient (D+/R-) was associated with increased p70S6k phosphorylation in CD19+ B lymphocytes (p = 0.0325). These associations were found to be independent of the trough levels of the immunosuppressive drugs. Conclusion: P70S6k phosphorylation in peripheral lymphocytes is associated with BKPyV reactivations and to a lesser extent with HCMV infections in renal transplant recipients.
CRIS-Team Scopus Importer:2021-04-16
Keywords: BK polyoma virus; human cytomegalovirus; p70 ribosomal S6 kinase; PyVAN; renal transplantation